Overlapping TATA-dependent and TATA-independent early promoter activities in the baculovirus gp64 envelope fusion protein gene. - Kogan, P H (1995)
In previous studies to characterize basal and activated transcription from the early promoter of the gp64 envelope fusion protein (efp) gene of the Orgyia pseudotsugata multicapsid nuclear polyhedrosis virus, the TATA box was identified as a functional element, essential for basal transcription from a minimal promoter construct. In the current study, we used discrete deletions and multiple point mutations that removed the functional TATA box from larger promoter constructs of the gp64 efp gene to reveal an overlapping TATA-independent transcriptional activity. TATA-independent transcriptional activity was inhibited in vitro by alpha-amanitin but not by tagetitoxin, demonstrating that like the TATA-dependent activity, the TATA-independent activity is mediated by RNA polymerase II. Using constructs in which the TATA box (TATATAA) was destroyed by substitution mutations, we identified four elements that are required for the TATA-independent activity. Two of the required elements, GATA (at -114) and CACGTG (at -104), were previously shown to specifically bind host transcription factors and activate transcription from the TATA-dependent wild-type gp64 efp promoter. The role of the early start site consensus CAGT sequence in TATA-independent transcription was also examined. Single-nucleotide substitution mutations in the CAGT sequence indicated that certain nucleotides within the CAGT start site were essential. In addition to the start site sequence and two upstream elements, a fourth essential element was identified in the 5' untranslated leader region (5'UTR). While the 5'UTR was not necessary for TATA-dependent transcription, deletion of a 10-bp 5'UTR sequence resulted in the loss of TATA-independent transcriptional activity. Although necessary, neither the GATA, CACGTG, start site region, nor 5'UTR element was alone sufficient for accurately initiated TATA-independent transcription from the consensus CAGT start site. Thus, the gp64 efp early promoter contains overlapping TATA-dependent and TATA-independent transcriptional activities. A number of common sequence elements (GATA, CACGTG, and start site CAGT) are involved in both of these activities, while one element (in the 5'UTR) is required only in the TATA-independent context.